Écouter l’inconscient du texte ? - Cuvillier, Élian (Etudes théologiques et religieuses, 2024)
This article offers five additional comments for the "Bible, literature and psychoanalysis" dossier: The Bible, literature and psychoanalysis have in common an infinite potential for meaning; the Bible is first and foremost symbolic and literature an infinite imaginary, while the psychoanalytical approach questions both; psychoanalysing a text involves listening to its unconscious; psychoanalytical listening to the biblical text is not a matter of scientific knowledge but of subjective truth; the poetic dimension of literature, including the biblical one, is fundamental.